2022
DOI: 10.1155/2022/7132159
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Brusatol Inhibits Proliferation and Metastasis of Colorectal Cancer by Targeting and Reversing the RhoA/ROCK1 Pathway

Abstract: Brusatol (BRU) is an important compound extracted from Brucea javanica oil, whose pharmacological effects are able to induce a series of biological effects, including inhibition of tumor cell growth, anti-inflammatory, antiviral, and antitumor. Currently, there are so few studies about the brusatol effects on colorectal cancer that its anticancer mechanism has not been clearly defined. In this study, we made an in-depth investigation into the brusatol effect towards the proliferation and metastasis of colon ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Brusatol (Bru; Figure 1 ) is a quassinoid plant extract isolated from the Brucea species plant, capable of inducing various biological effects, including antimalarial, anti-inflammatory, and antineoplastic. Its potential as an antineoplastic drug was reported in several solid tumors, such as pancreatic cancer (PC), non-small cell lung cancer (NSCLC), renal cell cancer (RCC), among others [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], as well as in hematological malignancies and particularly acute myeloid leukemia (AML) [ 18 ]. Previous investigations demonstrated that brusatol could act as a global protein synthesis inhibitor [ 19 ], while most studies reported it as an inhibitor of NRF2 signaling by reducing its protein levels through post-transcriptional mechanisms stimulating its ubiquitination and subsequent proteolysis [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brusatol (Bru; Figure 1 ) is a quassinoid plant extract isolated from the Brucea species plant, capable of inducing various biological effects, including antimalarial, anti-inflammatory, and antineoplastic. Its potential as an antineoplastic drug was reported in several solid tumors, such as pancreatic cancer (PC), non-small cell lung cancer (NSCLC), renal cell cancer (RCC), among others [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], as well as in hematological malignancies and particularly acute myeloid leukemia (AML) [ 18 ]. Previous investigations demonstrated that brusatol could act as a global protein synthesis inhibitor [ 19 ], while most studies reported it as an inhibitor of NRF2 signaling by reducing its protein levels through post-transcriptional mechanisms stimulating its ubiquitination and subsequent proteolysis [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they concluded that Ggps1 deletion disrupts the RhoA/Rock2 pathway, causing uterine contraction and parturition problems. Interestingly, Rho has been found to regulate MMP expression at various cell types [4244], raising the possibility that they are also co-involved in governing parturition process.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot assay was carried out in BBR and functional experiments in MCF7 and MDA-MB-231 cells. The detailed procedures have been described in our previous study [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…mRNA and cDNA were carried out as described previously [ 50 ]. The 2 −ΔΔCt approach was utilized to assess relative expression levels, with GAPDH as an internal control.…”
Section: Methodsmentioning
confidence: 99%